Research and innovation in Geography teaching as published in the Spanish Association of Geographers Bulletin: a bibliometric study - R. Sebastiá Alcaraz; E. M. Tonda Monllor (Boletín de la Asociación de Geógrafos Españoles)
Texto resumen.